Business Ethics in the Algorithmic Era: A Challenge Consumer Data Privacy and PDP Regulation - Saepulloh, Yusep; Andi, Rendi Rizki (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Amidst the euphoria of Industrial Revolution 4.0 and Society 5.0, data has emerged as "the new oil," fueling global economies while simultaneously triggering a fundamental ethical crisis. This study dissects the paradox of business ethics in Indonesia, where predictive algorithms often sacrifice human privacy for profit through the phenomenon of "surveillance capitalism". Utilizing a qualitative descriptive method with a juridical-normative approach, this research evaluates whether digital sovereignty has truly been achieved following the full implementation of Law Number 27 of 2022 concerning Personal Data Protection (PDP Law) on October 17, 2024. The analysis reveals a stark contrast: despite the legal framework, Indonesia's digital ecosystem in 2025 is still haunted by the absence of a functional independent supervisory body and persistent cybersecurity vulnerabilities, evidenced by the breach of 4.6 million citizens' data in West Java. Beyond mere legal compliance, this research proposes the Ethical Digital Entrepreneurship Model (EDEM) as a pragmatic framework to integrate values of honesty (shidq) and trust (amanah) into technological architecture. By repositioning data protection as a new form of Digital Corporate Social Responsibility (CSR), this article asserts that the future of digital business lies not just in algorithmic sophistication, but in moral integrity capable of reclaiming consumer trust.